Intonation Melody Therapy to Improve Language Production in Patients with Non Fluent Aphasia Disorder Post Stroke - Khamid, Abdul; Nugraha, Rizki Agung; Yunitri, Ninik; Agustina, Elis Nurhayati (STIKep PPNI Jawa Barat, 2024)
Aims: This Evidance Based Nursing Practice (EBNP) is to increase language production in patients with non-fluent aphasia post stroke. Methods: This EBNP method uses pre and post to see an increase in language production by assessing token test scores. By calculating the number of samples G-Power version 3.1.9.7 as many as 7 respondents. Data processing using Jamovi. Results: The analysis obtained using the t-test showed that the token test score experienced a significant change before and after the administration of intonation melody therapy (pValue <0.001), while the outcome of an increase in language production showed a significant change after administration of intonation melody therapy (pValue 0.896) with an average mean change mean 11.4 (95% CI: 6.28 -16.6) and moderate effect size (Cohen's d: 0.205). Conclusion: provision of melodic intonation therapy is proven effective in increasing language production in patients with post stroke non fluent aphasia.